Strategies to effect change in the ICU - Wallace, David J. (Curr Opin Crit Care, 2019)
PURPOSE OF REVIEW: To provide an update on implementation efforts in the care of critically ill patients, with a focus on work published in the last two years. RECENT FINDINGS: Only half of surveyed members of the multidisciplinary care team in the ICU were aware of the Choosing Wisely campaign, and of those that were, approximately one third reported no implementation of the recommendations. Barriers to implementation of the ABCDE bundle extend to beyond patient-level domains, and include clinician-related, protocol-related, and other domains. Prospective audit and feedback approaches have demonstrated moderate success for improving the quality of antibiotic prescription practices in the ICU. SUMMARY: Clinical research in intensive care has moved beyond simple discovery and dissemination. Best practices must be applied to effect change in ICU care, requiring the application of principles from implementation science. Future work should move beyond simple before-after evaluations to provide a stronger case for causal inference following implementation efforts.